KEBERKESANAN UNDANG-UNDANG MAKANAN DAN PRODUK HALAL DI MALAYSIA - Zakaria, Zalina (Jurnal Syariah, 2019)
The increasing awareness of Muslims all over the world on their obligation to consume food based on Islamic dietary law creates greater demand for halal food. Adulteration of food products nowadays creates perplexity among Muslims. Not everybody is educated in food science to understand the food ingredients and food products and as a result of that, Muslims become victims of the irresponsible people when they manipulate non-halal food and products as halal. At present, Department of Islamic Development Malaysia (JAKIM) is the sole body entrusted with the power to issue halal certification for products used by Muslims in this country by which is responsible to conduct inspections on the products and its manufacturing premises to ensure the authenticity of the certification. However, what we are concerned about is the lack of effective regulatory control in respect of food and products. This paper examines how far is the ineffectiveness as claimed together with some suggestions to be hoped at improving this matter so that our aim to become halal hub could be achieved.